High prevalence of vitamin A deficiency among children in Meghalaya and the underlying social factors - Nongrum, Melari Shisha; Kharkongor, Glenn Christo (Indian Journal of Child Health, 2015)
Objective: The objective was to estimate the prevalence of clinical vitamin A deficiency (VAD) in children 0-15 years, to determine the knowledge of nutrition and dietary practices, and to assess the social factors that are associated with vitamin A status in these children. Design: A cross-sectional study using household interviews with mothers of children 0-15 years and clinical examination of children for clinical VAD was conducted. A case-control study design was adopted to ascertain the knowledge and consumption of vitamin A rich foods and the associated social factors. Setting: Rural communities of Khasi tribal people in Pynursla Block, East KhasiHills, Meghalaya. Results: The prevalence of clinical VAD in children 0-15 years was 4.5% (95% confidence interval [CI] 3.32-5.98). The prevalence in school age (5-15 years) children was 5.9% (95% CI 4.12-7.68), higher than among pre-school children of 2.49% (95% CI 1.16-3.84). The community has a term for night blindness, Matiar, for which treatment is the intake of beef liver either in raw, boiled or roasted form. The control group had better knowledge of vitamin A rich food than the cases and they consumed 28% more vitamin A rich food than the cases while intake of wild edibles was higher in case group by 9%. Maternal education and familysize were found to be significantly associated with vitamin A status of children. Conclusion: VAD is a public health problem among children 0-15 years in Pynrusla Block of East Khasi Hills District, Meghalaya. In order to effectively address this problem, it is essential to enhance the knowledge of nutrition and appropriate diets and to encourage the consumption of traditional foods especially locally available vitamin A rich foods.